Beyond the rules: an integrative review of parental perspectives on safer infant sleep in shared environments - Grubb, Carly; Young, Jeanine; Downer, Terri; D’Souza, Levita (Frontiers in Public Health, 2025)
BackgroundDespite public health campaigns promoting infant sleep safety, SUDI (including SIDS and fatal sleep accidents) remains one of the most significant contributors to post-neonatal infant death in many high-income countries. Bedsharing remains common despite predominant risk elimination guidelines, with many families struggling to follow rigid rules of avoidance. Risk minimisation considers the complexities of family life and recognises most infant deaths in shared sleep environments are associated with additional risk factors.Purpose and methodsIntegrative review methodology was used to investigate the information parents need to minimise risk for infants under 12 months who share a sleep surface. Database searches included Scopus, CINAHL, PubMed, PsycNET and Emcare to identify peer-reviewed publications published January 2013–March 2025. Quality appraisal was undertaken using the QuADs tool.ResultsA total of 60 articles met eligibility criteria. Twelve themes were generated from the data and grouped under four key domains: 1. Challenges in creating safer shared sleep environments, 2. Solutions/strategies used by parents to address challenges, 3. Family experiences when risk factors are present, and 4. Information needs of parents and caregivers. Families reported sharing sleep with infants, intentionally and accidentally, including those at a higher risk of SUDI. Bedsharing often occurs outside of a conscious parental ‘choice’, while families frequently refrain from disclosing bedsharing practices to health professionals. In the absence of formal guidance on safer shared sleep strategies, families generated their own solutions potentially increasing risk.ConclusionParents need universal access to non-judgmental, neutrally-worded support that allows them to ‘prepare to share’ and employ strategies to enhance infant sleep safety wherever, and whenever it occurs.